Scientific and Design Stances - Saariluoma, Pertti (Human Technology, 2010)
Human technology interaction is a strange field of expertise, because both academics and industry are interested in it. And yet, every now and then, it becomes apparent that academics and industry do not always see eye to eye (Carroll, 1997). They seem to think in different manner. While scientists look for how things are, industry mostly seeks out how things should be. Indeed, sometimes two very different stances behind the basic thinking of the two important human–technology interaction (HTI) communities surface.